2013
DOI: 10.1056/nejmoa1110039
|View full text |Cite
|
Sign up to set email alerts
|

Short-Course Antiretroviral Therapy in Primary HIV Infection

Abstract: BackgroundShort-course antiretroviral therapy (ART) in primary human immunodeficiency virus (HIV) infection may delay disease progression but has not been adequately evaluated. MethodsWe randomly assigned adults with primary HIV infection to ART for 48 weeks, ART for 12 weeks, or no ART (standard of care), with treatment initiated within 6 months after seroconversion. The primary end point was a CD4+ count of less than 350 cells per cubic millimeter or long-term ART initiation. ResultsA total of 366 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
129
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(137 citation statements)
references
References 32 publications
8
129
0
Order By: Relevance
“…Disappointingly, time off treatment was not significantly longer than the 48‐week treatment period and the increase in CD4 count on long‐term ART was similar across all three groups. In contrast to the SMART trial, there were no adverse effects on clinical outcomes 51, 210. Adult case series from prospective observational cohort studies and the results of the Agence Nationale de Recherche sur le SIDA (ANRS) Virological and Immunological Studies in Controllers after Treatment Interruption (VISCONTI) study suggest that some patients with different genetic characteristics and characteristic CD8 cell response to HIV, after prolonged treatment of primary HIV infection, can control HIV replication post treatment interruption for at least several years 211, 212.…”
Section: Stopping Treatment and Treatment Interruptionsmentioning
confidence: 84%
“…Disappointingly, time off treatment was not significantly longer than the 48‐week treatment period and the increase in CD4 count on long‐term ART was similar across all three groups. In contrast to the SMART trial, there were no adverse effects on clinical outcomes 51, 210. Adult case series from prospective observational cohort studies and the results of the Agence Nationale de Recherche sur le SIDA (ANRS) Virological and Immunological Studies in Controllers after Treatment Interruption (VISCONTI) study suggest that some patients with different genetic characteristics and characteristic CD8 cell response to HIV, after prolonged treatment of primary HIV infection, can control HIV replication post treatment interruption for at least several years 211, 212.…”
Section: Stopping Treatment and Treatment Interruptionsmentioning
confidence: 84%
“…The majority of rebounds in this group occurred following treatment discontinuation, with the proportion of patients experiencing rebound while reportedly still receiving cART being similar across groups. Reasons for treatment discontinuation in this group are unknown; however, it is possible that some of these individuals were enrolled in trials of treatment interruption strategies that were undertaken during this time period 14. However, this trend towards more treatment interruption in those starting cART with a high CD4 count raises some concerns.…”
Section: Discussionmentioning
confidence: 99%
“…A series of prior studies have indeed shown that short-term antiretroviral treatment in acute or early HIV-1 infection can preserve B-cell-mediated (6) and T-cellmediated (7) immune function, supports the development of HIV-1-specific CD4 T cell responses (8), limits the diversity of circulating viral strains (9), and in some cases facilitates spontaneous control of low-level HIV-1 viremia after treatment discontinuation (10,11). Recently, data from three prospective, randomized-controlled clinical trials indicated that a 1-to 2-year antiretroviral treatment course started during acute or early HIV-1 infection can lead to reduced HIV-1 set point viremia after treatment discontinuation (12)(13)(14), providing compelling evidence for beneficial effects of antiretroviral therapy initiation dur-ing the earliest stages of HIV-1 infection. Nevertheless, such effects were modest and not sustained long term, indicating that short-term therapy in primary infection may not significantly affect the eventual HIV-1 disease outcome.…”
mentioning
confidence: 99%